Functionalized 3D-printed GelMA/Laponite hydrogel scaffold promotes BMSCs recruitment through osteoimmunomodulatory enhance osteogenic via AMPK/mTOR signaling pathway - Linquan Zhou; Chengcheng Zhang; Tengbin Shi; Dingwei Wu; Huina Chen; Jiaxin Han; Dehui Chen; Jinxin Lin; Wenge Liu (Materials Today Bio)
The migration and differentiation of bone marrow mesenchymal stem cells (BMSCs) play crucial roles in bone repair processes. However, conventional scaffolds often lack of effectively inducing and recruiting BMSCs. In our study, we present a novel approach by introducing a 3D-bioprinted scaffold composed of hydrogels, with the addition of laponite to the GelMA solution, aimed at enhancing scaffold performance. Both in vivo and in vitro experiments have confirmed the outstanding biocompatibility of the scaffold. Furthermore, for the first time, Apt19s has been chemically modified onto the surface of the hydrogel scaffold, resulting in a remarkable enhancement in the migration and adhesion of BMSCs. Moreover, the scaffold has demonstrated robust osteogenic differentiation capability in both in vivo and in vitro environments. Additionally, the hydrogel scaffold has shown the ability to induce the polarization of macrophages from M1 to M2, thereby facilitating the osteogenic differentiation of BMSCs via the bone immune pathway. Through RNA-seq analysis, it has been revealed that macrophages regulate the osteogenic differentiation of BMSCs through the AMPK/mTOR signaling pathway. In summary, the functionalized GelMA/Laponite scaffold offers a cost-effective approach for tailored in situ bone regeneration.